1977
DOI: 10.1139/x77-032
|View full text |Cite
|
Sign up to set email alerts
|

Stump injections with soil fumigants to eradicate Armillariellamellea from young-growth ponderosa pine killed by root rot

Abstract: Root rot caused by Armillariellamellea (Vahl ex Fr.) Karst. creates unproductive disease centers in young-growth ponderosa pine (Pinusponderosa Laws.) after removal of the old-growth timber. The fungus persists in stumps in these centers keeping the land unproductive indefinitely. Armillariellamellea was effectively eradicated from infected stumps by insitu fumigation with methyl bromide, Vorlex, chloropicrin, carbon disulfide, and Vapam. The fungal antagonist Trichoderma appeared to be unaffected by the fumig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

1990
1990
1998
1998

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 0 publications
0
14
0
1
Order By: Relevance
“…Fungicides are ineffective against Armillaria and similar root rots, but soil fumigation may be worthwhile (e.g. Filip and Roth 1977).…”
Section: Diseases In Seed Orchardsmentioning
confidence: 99%
“…Fungicides are ineffective against Armillaria and similar root rots, but soil fumigation may be worthwhile (e.g. Filip and Roth 1977).…”
Section: Diseases In Seed Orchardsmentioning
confidence: 99%
“…CS 2 has known bacteriostatic (Bremner and Bundy, 1974;Malhi and Nyborg, 1982), fungicidal (Bliss, 1951;Munnecke et al, 1973;Filip and Roth, 1977), nematicidal (Chandler, 1969), and insecticidal (Punj and Girish, 1969) properties. Some plants emit CS 2.…”
Section: Introductionmentioning
confidence: 99%
“…The most frequently advocated methods of control against Armillaria species are physical removal of stumps and large roots (Doepel, 1962;Roth, Rolph & Cooley, 1980), soil fumigation around infected hosts or direct injection of fumigants into infected hosts (Filip & Roth, 1977;Munnecke et al, 1981) However, these methods can be cost-prohibitive in forests, and the use of fumigants toxic to other soil microorganisms, fauna and stump decay fungi, may render them environmentally unacceptable (SchCitt, 1985). Biological control methods may be a viable alternative, as ecological studies and field inoculation trials in other parts of the world have indicated that saprophytic stump-inhabiting fungi may be natural and/or potential competitors against root infecting fungi such as Armillaria species, Heterobasidion annosum (Fr.)…”
Section: Introductionmentioning
confidence: 99%